Smart system to control lighting in a smart library - Ouissale Elansari; Hicham Jamouli (IAES International Journal of Artificial Intelligence (IJ-AI), 2026)
Smart light controllers revolutionize energy efficiency and convenience by controlling lights with precision. The main problem with such control structures is that the existing lighting systems are outdated and inefficient in places such as libraries, leading to unnecessary energy consumption. In this study, we propose the implementation of an intelligent light-emitting diode (LED) lighting control system that optimizes energy in libraries. The system utilizes passive infrared (PIR) sensors and a counter mechanism. When an aisle is occupied, the LEDs operate in highlight mode; however, they switch to medium-light mode when no presence is detected for a predetermined period. For this process, we propose a new control system with the random forest prediction algorithm for displacement patterns. We also designed a mathematical algorithm with three matrices derived from previous work on lighting. The algorithmic process is applied to ensure that the proposed system has enhanced maintainability, the simulation methodology generated scenarios based on occupancy data collected from real library environments, MATLAB was used to create dynamic simulations that reflected these user behaviors, with the power consumption of each LED calculated over an eight-hour operating period, the proposed system achieves potential savings between 23% to 39%.